1992
DOI: 10.1103/physreva.45.r5369
|View full text |Cite
|
Sign up to set email alerts
|

Sine-Gordon kink-antikink generation on spatially periodic potentials

Abstract: A spatially periodic perturbation can lead to a breakup of large-amplitude sine-Gordon breathers into kink and anti kink solutions, each oscillating around a minimum of the perturbing potential. This behavior can be understood by studying the effective potential experienced by the breather (bound kink-antikink) or the (free) kink-antikink solution as long as kink and antikink are sufficiently far apart. The resulting kinks and antikinks move independently and nearly radiationlessly in the presence of the pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…(6) which shows that 'l/;x is playing a role in the smallamplitude breather evolution. On the contrary, global energetic considerations are more suitable explanations of the nonradiative, f{ -f{ breakup of large-amplitude breathers, as we will report elsewhere [12]. We also want to stress again the fact that we have performed similar simulations on the NLS system [11] and find the same kind of "phase diagram," which is a good indication that NLS-like approaches to the SG breather problem can be helpful: for instance, Eqs.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…(6) which shows that 'l/;x is playing a role in the smallamplitude breather evolution. On the contrary, global energetic considerations are more suitable explanations of the nonradiative, f{ -f{ breakup of large-amplitude breathers, as we will report elsewhere [12]. We also want to stress again the fact that we have performed similar simulations on the NLS system [11] and find the same kind of "phase diagram," which is a good indication that NLS-like approaches to the SG breather problem can be helpful: for instance, Eqs.…”
mentioning
confidence: 66%
“…We will show that they indeed provide some useful information, without overly involved algebra. With the basic assumption that the effect of the potential on the breather is to allow it to move, without changing its shape, it is possible to derive [further detail is planned to be given elsewhere [12], but the basis is the fact that the evolution under Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of a free kink and antikink into a breather has been addressed in [62] in the presence of spatially periodic perturbation. An external dc driving force in the absence of damping for a sufficiently large magnitude of the force causes the breather to split into a kink-antikink pair, while for a small driving force the breather excitations lead to stationary modes [63].…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that length-scale competition is crucial for understanding dynamics of both one-dimensional nonlinear Schrodinger (NLS) and onedimensional sine-Gordon (SG) systems driven by a static, spatially periodic parametric potential [1][2][3]. The picture that has emerged is that the length-scale competition between the width of a breather and the spatial period of the external potential controls the particlelike coherence of the breather.…”
Section: Introductionmentioning
confidence: 99%